Induction of vacuolization in spermatozoa from men with oligoasthenoteratozoospermia after cryopreservation with glycerol and polyvinylpyrrolidone - Petrushko, M. P.; Pavlovich, O. V.; Puhovkin, A. Yu.; Kovalenko, I. F.; Pinyaev, V. I.; Yurchuk, T. O. (Морфологія / Morphologia / Morfologìâ, 2020)
Background. The two–step method using penetrating cryoprotectant glycerol is a routine for cryopreservation of spermatozoa from men with normal spermatogenesis. However, the use of this freezing method in the case of oligoasthenoteratozoospermia (OAT) leads to additional cells damage and there is a need to search for new effective cryopreservation method. The sperm vacuolization inherent in male gametes plays a negative role, reducing the fertilizing ability of cells. Objective. The aim of the study was to assess the degree of vacuolization induced in human OAT sperm after cryopreservation by a two–stage method using glycerol and polyvinylpyrrolidone (PVP), molecular mass 360000. Methods. The isolated sperm fraction was divided into 3 groups: group I – native spermatozoa, II – spermatozoa cryopreserved by the two–stage method with 10% glycerol, group III – spermatozoa cryopreserved by the two–stage method with 10% PVP. Results. About 5% of spermatozoa contained vacuoles in group I. The number of spermatozoa with one small vacuole increased to (19.68 ± 2.27)% in group II. And in group III the number of cells without vacuoles was comparable with native spermatozoa: 95.59 ± 1.59 and (96.09 ± 2.02)%, respectively. Conclusion. Thus, the use of a penetrating cryoprotectant of glycerol at 10% concentration for two–stage method cryopreservation of human spermatozoa initiates the vacuoles formation while the use of non–penetrating PVP can prevent vacuolization.